Nonalcoholic fatty liver disease is associated with an almost twofold increased risk of incident type 2 diabetes and metabolic syndrome. Evidence from a systematic review and meta‐analysis. Issue 5 (May 2016) - Ballestri, Stefano; Zona, Stefano; Targher, Giovanni; Romagnoli, Dante; Baldelli, Enrica; Nascimbeni, Fabio; Roverato, Alberto; Guaraldi, Giovanni; Lonardo, Amedeo
Abstract: Background and Aim: The magnitude of the risk of incident type 2 diabetes (T2D) and metabolic syndrome (MetS) among patients with nonalcoholic fatty liver disease (NAFLD) is poorly known. We gauged the risk of developing T2D and MetS in patients with NAFLD diagnosed by either serum liver enzymes (aminotransferases or gamma‐glutamyltransferase [GGT]) or ultrasonography. Methods: Pertinent prospective studies were identified through extensive electronic database research, and studies fulfilling enrolment criteria were included in the meta‐analysis. Results: Overall, in a pooled population of 117020 patients (from 20 studies), who were followed‐up for a median period of 5 years (range: 3–14.7 years), NAFLD was associated with an increased risk of incident T2D with a pooled relative risk of 1.97 (95% confidence interval [CI], 1.80–2.15) for alanine aminotransferase, 1.58 (95% CI, 1.43–1.74) for aspartate aminotransferase, 1.86 (95% CI, 1.71–2.03) for GGT (last vs first quartile or quintile), and 1.86 (95% CI, 1.76–1.95) for ultrasonography, respectively. Overall, in a pooled population of 81411 patients (from eight studies) who were followed‐up for a median period of 4.5 years (range: 3–11 years), NAFLD was associated with an increased risk of incident MetS with a pooled relative risk of 1.80 (95% CI, 1.72–1.89) for alanine aminotransferase (last vs first quartile or quintile), 1.98 (95% CI, 1.89–2.07) for GGT, and 3.22 (95% CI, 3.05–3.41) for ultrasonography, respectively. Conclusions: Nonalcoholic fatty liver disease, as diagnosed by either liver enzymes or ultrasonography, significantly increases the risk of incident T2D and MetS over a median 5‐year follow‐up.